2D MXene: A Potential Candidate for Photovoltaic Cells? A Critical Review. Issue 10 (15th February 2022) - Saeed, Muhammad Ahsan; Shahzad, Asif; Rasool, Kashif; Mateen, Fahad; Oh, Jae‐Min; Shim, Jae Won
Abstract: The 2D transition metal carbides/nitrides (2D MXenes) are a versatile class of 2D materials for photovoltaic (PV) systems. The numerous advantages of MXenes, including their excellent metallic conductivity, high optical transmittance, solution processability, tunable work‐function, and hydrophilicity, make them suitable for deployment in PV technology. This comprehensive review focuses on the synthesis methodologies and properties of MXenes and MXene‐based materials for PV systems. Titanium carbide MXene (Ti3 C2 T x ), a well‐known member of the MXene family, has been studied in many PV applications. Herein, the effectiveness of Ti3 C2 T x as an additive in different types of PV cells, and the synergetic impact of Ti3 C2 T x as an interfacial material on the photovoltaic performance of PV cells, are systematically examined. Subsequently, the utilization of Ti3 C2 T x as a transparent conductive electrode, and its influence on the stability of the PV cells, are discussed. This review also considers problems that emerged from previous studies, and provides guidelines for the further exploration of Ti3 C2 T x and other members of the 2D MXene family in PV technology. This timely study is expected to provide comprehensive understanding of the current status of MXenes, and to set the direction for the future development in 2D material design and processing for PVs. Abstract : Recent progress on MXene‐based PVs is discussed. Synthesis procedures and properties of MXene are presented. The role of MXene as an additive, interfacial layer, and as a conductive electrode in PVs is comprehensively studied. Later, the influence of MXene on the stability of PVs is described. Finally, guidelines to overcome the challenges of MXene based materials for PVs are provided.